Rheological properties and fractal-rheology analysis of peanut protein isolate suspension - Bi, Chonghao; Chi, Shangyi; Hua, Zhe; Li, Dong; Huang, Zhigang; Liu, Yi (International Journal of Agricultural and Biological Engineering, 2020)
This study focuses on the non-linear rheological property and microstructure of peanut protein isolate (PPI) aggregation suspension. The impact of higher harmonics (I3 and I5) on fundamental stress wave during large amplitude oscillatory shear test was studied. Rheological test show that storage modulus G′ and loss modulus G″ increased with increasing PPI concentration. The non-linear viscoelastic properties of PPI suspension with different concentration were investigated. Using confocal laser-scanning microscopy method, this research explored the microstructure of PPI suspension as well as the fractal dimensions. The new critical strain indirect method combined with Wu-Morbidelli model to calculate the fractal dimension (2.9225) is very close to the actual fractal dimension (2.9206). Fourier Transform Rheology was adopted to get the new critical strain for fractal dimension calculation, which was proved to be feasible.Keywords: peanut protein isolate suspension, rheological property, microstructure, fractal analysisDOI: 10.25165/j.ijabe.20201306.5717Citation: Bi C H, Chi S Y, Hua Z, Li D, Huang Z G, Liu Y. Rheological properties and fractal-rheology analysis of peanut protein isolate suspension. Int J Agric & Biol Eng, 2020; 13(6): 220–226.